Eclipse (2016), volume 2 ebook - Kaplan, Zack (Eclipse (2016), 2018)
In a world where sunlight burns people alive, Cielo Brandt, heiress of the city's most powerful company, and her savior David Baxter, have both survived a killer who didn't burn in the sunlight. Now, both want answers about his origins; Cielo investigates the city's underground and her father's company, while Bax braves the postapocalyptic wasteland and the discovery of another who is immune to the sun's rays. Collects ECLIPSE #5-8. Author: Zack Kaplan. Illustrator: Giovanni Timpano . 2017 Top Cow Productions, Inc.